Pangan Dika Tradition in Islamic Guidance Practice at the Cikalama Islamic Traditional School (Pesantren) - Tajiri, Hajir (Ilmu Dakwah: Academic Journal for Homiletic Studies, 2023)
Various methods are used in the da'wah (guidance) of the Islamic religion, especially in Islamic boarding schools, with the aim of providing an understanding of Islam so that it is more concise and easier, so that the guidance material is effectively understood by the students. This effort is known by various names, such as in the form of modules, pocket books, summaries, summaries and policy briefs, or at a certain level, book reviews. The article aims to reveal the use of the Pangan Dika book as a way and approach to briefly understand Islam which is practiced at the Cikalama Sumedang Islamic Traditional School. The research uses a qualitative approach. Data collection used by observation, interview and documentation methods. Based on the research results, it is known that besides being used as a handbook, Pangan Dika is also called a "method", namely the "Pangan Dika method" using the bandongan method, delivered by a teacher with the rhythm of the song or style of Pangan Dika whose contents include jampe wudlu ( ablution prayer), jampe salat (prayer prayer), kawula boga pangeran (statement of one's attitude towards having God), wirid (special and continuous prayer), hukum, aqaid (pillars of belief), parukunan (harmonies) pillars of prayer, wudlu, etc.), etiquette towards teachers, and the nature of God 20. The Pangan Dika method is practiced regularly and gradually, every student is encouraged to be able to memorize the Pangan Dika text and teach it to others when they have mastered it. Teaching Islamic material in the form of Dika Food has an impact on acceptance and makes understanding easier.